AESTHETICS OF MUSICAL EMBODIMENT ON THE CONCEPT OF MUSIC AS PRESENCE (USING PHILIPPINE MUSIC EXAMPLES) - JosÃ© S. Buenconsejo (Proceeding IICACS, 2019)
This paper compares the aesthetics of three songs from two musical traditions (one from the indigenous Manobo community in non-Islamic Mindanao Island and two from urban popular songs). It argues that song is not merely a personal expression but a performance (song-act) that indicates concrete